Reducing the carbon emissions from Qianxi tomato fruits preservation by cold atmospheric plasma - Jin, Tao; Chen, Yan; Dai, Chenwei; Deng, Jimin; Xu, Qinghua; Wu, Zhengwei (International Journal of Agricultural and Biological Engineering, 2023)
China has pledged to reach its dual-carbon goals (i.e., carbon peak and carbon neutrality) at the end of 2060. To reduce carbon emission in food preservation industry, the preservation effects of cold atmospheric plasma intermittent treatment (1 min/6 h each day, PL4) combined with 15°C and 4°C only on Qianxi tomato fruits during 7 d storage were investigated. Results indicated that the firmness, L*, sensory taste, glutathione (GSH) content, mineral (Fe, P, K) content, polyphenol oxidase activity of PL4 tomatoes were significantly increased than that in Control during earlier period storage, with worse weight loss, titratable acid, a*, b*, lycopene content, •OH radical scavenging capacity and same moisture content, total soluble solids, polysaccharide content, total phenolics content, total flavonoid content, ascorbic acid content, 1,1-diphenyl-2-picrylhydrazyl radical scavenging capacity, pectin methylesterase activity. Moreover, the power and R134a consumption of PL4 were highly decreased by around 56.4 kW•h and 0.3 g respectively during whole storage as compared to Control, and reduced more than 99.8% carbon emission based on equipment using stage. All in all, this study illustrated that PL4 treatment can be applied as an ecofriendly, low carbon and sustainable preservation strategy for short-term storage of fruits under 4°C or higher temperature.Keywords: cold atmospheric plasma, carbon reduction, Qianxi tomato fruits, food preservationDOI: 10.25165/j.ijabe.20231605.8154Citation: Jin T, Chen Y, Dai C W, Deng J M, Xu Q H, Wu Z W. Reducing the carbon emissions from Qianxi tomato fruits preservation by cold atmospheric plasma. Int J Agric & Biol Eng, 2023; 16(5): 213-220.